Agrobiodiversity Index Report 2021: Assessing Mediterranean food systems - Jones, Sarah K.; Remans, Roseline; Dulloo, Mohammad Ehsan; Estrada-Carmona, Natalia; Bailey, Arwen; Grazioli, Francesca; Villani, Chiara; Bissessur, Prishnee (Bioversity International, 2022)
The Agrobiodiversity Index report 2021: Assessing Mediterranean Food Systems analyses the state of agrobiodiversity in a set of Mediterranean countries, looking at agrobiodiversity in food consumption, production, and genetic resource conservation. It sheds light on the actions and policies countries are already taking to use and preserve their agrobiodiversity. It also provides concrete recommendations on what practices and policies countries could strengthen or put in place to mainstream agrobiodiversity into their food systems. The report focuses on ten target countries: Algeria, Egypt, France, Italy, Lebanon, Libya, Morocco, Spain, Syria, and Tunisia. These countries were selected to include all countries with at least 1% of the Mediterranean region population and where the official language could be understood by the Agrobiodiversity Index team (to enable analysis of commitment levels in policy documents), namely: English, French, Spanish, Italian or Arabic. The report contributes to strengthening evidence on the benefits of agrobiodiversity in Mediterranean countries for healthy people and a healthy planet. The report also fed into the second international Agrobiodiversity Congress, held in 2021, to inform and guide the discussions during the event. Key messages from the report will be used to stimulate discussions at country level on the policy actions needed to better integrate agrobiodiversity into the food system and increase adherence to the Mediterranean diet.